Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1523/jneurosci.1392-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

The Neural and Cognitive Time Course of Theory of Mind

Abstract: Neuroimaging and neuropsychological studies implicate both frontal and temporoparietal cortices when humans reason about the mental states of others. Here, we report an event-related potentials study of the time course of one such “theory of mind” ability: visual perspective taking. The findings suggest that posterior cortex, perhaps the temporoparietal cortex, calculates and represents the perspective of self versus other, and then, later, the right frontal cortex resolves conflict between perspectives during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
119
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(138 citation statements)
references
References 32 publications
15
119
2
Order By: Relevance
“…Specifically, individuals may be engaging in inner speech while they actively think about distrusting the individual depicted. In terms of connectivity, there is evidence that the IFG is functionally connected with the TPJ during theory-of-mind tasks (McCleery, Surtees, Graham, Richards, & Apperly, 2011). The results from this study support the role of the IFG in the cognitive control and the valuation of attitudes of trust and distrust.…”
Section: Discussionsupporting
confidence: 73%
“…Specifically, individuals may be engaging in inner speech while they actively think about distrusting the individual depicted. In terms of connectivity, there is evidence that the IFG is functionally connected with the TPJ during theory-of-mind tasks (McCleery, Surtees, Graham, Richards, & Apperly, 2011). The results from this study support the role of the IFG in the cognitive control and the valuation of attitudes of trust and distrust.…”
Section: Discussionsupporting
confidence: 73%
“…The dlPFC is well-documented to code for holding simultaneously and decoupling one's and other's perspective Gallagher and Frith, 2003). Especially, the right dlPFC is critically involved in the cognitive monitoring (Vogeley et al, 2001) and inhibition of one's perspective when reasoning about the perspective of someone else (Goel and Dolan, 2003;Decety, 2003, 2004;Samson et al, 2005;McCleery et al, 2011;Van der Meer et al, 2011). Concordant with these findings, stroke patients with right MFG/dlPFC damages are significantly impaired in cognitive tasks requiring patients to inhibit their egocentered perspective (Samson et al, 2005).…”
Section: Modulations Of the Mns Nodes Activation Between Empathy Andmentioning
confidence: 78%
“…The temporo-parietal and prefrontal cortices are two major areas of the mentalizing network (MENT) that sustain reasoning about the beliefs, thoughts, and intentions of others while adopting their point of view (Saxe and Kanwisher, 2003;Samson et al, 2005). Especially, data from both brain-damaged patients and non-clinical populations converge on the role of the left TPJ, showing that it underlies the ability to code for the visuospatial perspective of someone else (heterocentered) (Samson et al, 2004) and ownership of perspective during ToM/mentalizing tasks Aichhorn et al, 2006;McCleery et al, 2011). Within the right PFC, the vmPFC is known to calculate and represent another individual's psychological/mental viewpoint (Gallagher et al, 2000;Frith and Frith, 2003).…”
Section: The Multidimensional Model Of Empathymentioning
confidence: 99%
“…On trials when the avatar can see all of the dots, the visual perspectives of the avatar and of the participant are consistent; whereas on trials when the avatar can see only some of the dots, the two visual perspectives are inconsistent. A number of behavioural experiments have confirmed that response times to judge self-perspective are longer when the two visual perspectives are inconsistent, than when they are consistent Qureshi et al, 2010;McCleery et al, 2011;Santiesteban et al, 2014). This result has been taken to support the claim that the avatar's visual perspective is spontaneously processed, under the assumption…”
mentioning
confidence: 72%